Examinations Problems in the Russian Literature Course read by professor Loboiko I. N. at the Vilnius State University in the beginning of the XIX century - Kaupuža, A. (Literatūra, 1969)
Examining the minutes of literature department in 1822 - 1823 has made it possible to restore the problems of examination questions in Russian literature course read by professor Loboiko l. N. It has also enabled the investigator to make an attempt to throw some light on the content of literature course. The minutes are to be found in the Central State History Archives of the Lithuanian SSR. The analysis of the examination questions reveals that the content of the lectures by professor l. N. Loboiko was diverse (the problems of literature history and theory, the history or Russia, the evolution of Russian culture were touched upon). But it is very likely that the account was eclectic.